Arguments for Csr-Based Sustainable Competitiveness of Multinationals in Emerging Markets (Part II) - Claudia; Herciu Mihaela (Studies in Business and Economics, 2015)
The (two parts of the) paper aims to bring into discussion the case of CSR-based sustainable competitiveness of multinationals in emerging market economies, through an interdisciplinary approach (international business and strategic management) applied to a multilevel analysis (country and company). The main conclusion of the paper is that, despite the circumstances that nowadays characterize international business in general and the emerging market economies in particular, such a transformation in business models is not only desirable, but mandatory. Key arguments in favor of this assumption are found (both theoretically and empirically) at global/general level and, as well, at the emerging market economies’ level.